Development and understanding of a model V2O5/anatase TiO2(101) SCR catalyst - Paulsson,Johanna (2023)
A model V2O5/ anatase TiO2(101) SCR catalyst is studied with the purpose of developing and understanding the reaction mechanism through which this catalyst reduces NOx. Several reaction mechanisms have been proposed for this catalyst in the past, but there is still no agreement on which of these describe the reaction the best, if any. Two coverages of 2 ML and 0:33 ML V/ anatase TiO2 and the oxidation of these surfaces are studied experimentally using XPS and NAPXPS. The results show evidence of chemisorption of VO2 and V2O3 at low oxygen pressure and V2O5 at near-ambient pressures. Furthermore, from the vanadia spectra it can be suspected that there are two types of vanadium deposits, one phycisorbs on the surface and starts as a V(0) like species and then can be oxidized to higher binding energies, and another one that is substituted for the Ti species and then can be oxidized further when exposed to high pressure oxygen, high dosage of oxygen or atomic oxygen.